Effects of Carbohydrate Diet Programs on Urine Ketones Positiveness with Long Time on a Diet 1 Year, 2 Years and 3 Years - Maya, Dyah Astining; Pauzi, Iswari; Zaetun, Siti; Jiwantoro, Yudha Anggit (Jurnal Analis Medika Biosains (JAMBS), 2023)
Carbohydrate diet is a diet pattern that reduces carbohydrate consumption. Therefore, the body will use fat as an alternative energy source. The continuous use of fat causes the accumulation of fatty acids so that it often causes ketone positivity in the urine. Objective : Find out the effect of a carbohydrate diet program on the positivity of urine ketones. Method : This research is an analytic observational study with a cross sectional approach. The sample used was urine from respondents who had been on a carbohydrate diet for 1 year, 2 years and 3 years, then urine ketones were examined using the dipstick method. Data analysis was carried out using the Chi-Square test with a confidence value (α = 0.05). Result : The sample in this study amounted to 45 samples, with a total of 23 samples of positive ketones and 22 samples of negative ketones. The results of the Chi Square test obtained an Asymp. sig value of 0.009 <0.05 (α) which indicates that the carbohydrate diet program has a significant effect on the positivity of urine ketones.